Complimenting as a Conversation Opener: a Strategy in Teaching English Speaking Proficiency - Yohannes Telaumbanua (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2012)
The speech act of paying compliment (“you are looking good”) to someone is the attempt to establish the social relationship and ties solidarity between the communicators. In addition, it attributes credit to someone other than the speaker; usually the person addressed, for some “good” (possession, characteristic, skill, etc.) which is positively valued by the speaker and the hearer. Furthermore, the act of responding it is an interlocutor’s acceptance (“Thanks, Thank you”) and non-acceptance (“it is really quite old”) of the compliments. In conjunction with English teaching and learning process, the attempt to compliment and respond it can be used as a strategy to help the EFL learners able to open a conversation or a short talk with their classmates. The EFL lecturers/teachers will bridge the learners to strike up their conversations/short talks by providing some conversations/short talks’ situations. The situations, which relate to their friends’ possessions, characteristics, or skills, are used to attribute their credits as conversation opener.